The meaning and structure of the inaugural address by John F. Kennedy in 1961 : A systemic functional analysis = Cấu trúc và ngữ nghĩa bài diễn văn nhậm chức của John F. Kennedy năm 1961 : Phân tích theo quan điểm chức năng hệ thống - Nguyễn, Thị Kim Oanh, 1987- (University of Languages and International Studies, 2017)
This study applies systemic functional grammar in order to investigate the meaning and structure of the inaugural address by John F. Kennedy in 1961. Based on the frameworkof systemic functional grammar developed by Halliday, the study focuses on analyzing the text in terms of language functions (three metafunctions) and cohesion (grammatical and lexical cohesion). The findings revealthat in terms of transitivity, material process is predominant; in terms of mood, declarative mood is in the largest use; and in terms of theme, topical theme which forms unmarked one is the most notable feature in the whole text. Besides, grammatical cohesion presented by reference, conjunctive devices and structural parallelism and lexical cohesion illustrated through repetition, synonymy, and antonymy make a great contribution to the cohesion and coherence of the text. Undeniably, the analysis proves that this text is really meaningful, concise, and highly cohesive with the diversified uses of lexis and structures and so systemic functional grammar is an effective tool for analyzing the structure and meaning of a particular text.